2020
DOI: 10.1108/jima-01-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Improving the satisfaction and loyalty of BPJS healthcare in Indonesia: a Sharia perspective

Abstract: Purpose The purpose of this study is to analyze how to improve the satisfaction and loyalty of Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) health patients in Indonesia based on services in Islamic hospitals, where the service quality was analyzed from a Sharīʿah perspective. Design/methodology/approach The sample for this study was 470 Muslim patients from BPJS health, 248 from large Islamic hospitals and 232 from small Islamic hospitals in Central Java, Indonesia. Overall, the respondents were from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
3
16
0
1
Order By: Relevance
“… 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 24 Satisfaction can be improved through variables such as reliability, empathy, and responsiveness, and the loyalty of patients will be strongly affected by satisfaction. 25 Abekah-Nkrumah et al 26 found that the ownership of health facility will not directly affect PS and PL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, tabligh variable is related and close enough to customer satisfaction indicator such us, responsiveness and reliability which are demanded by customer while served in Islamic Bank (Ratnawati & Kholis, 2019;Ratnawati, Cokrohadisumarto, & Kholis, 2020). The last, fathana or intelligence is factor that shows Islamic Bank is up to date with recent and latest development.…”
Section: Discussionmentioning
confidence: 92%
“…Public satisfaction can be measured by a number of indicators, namely reliability, responsiveness (Kant & Jaiswal, 2017), empathy (Ratnawati et al, 2020), professionalism, information availability, staff attitude, (Lanin & Hermanto, 2019), image (Coutinho et al, 2019). The satisfaction of street vendors relocation in the city of Yogyakarta is basically influenced by the culture of the city government of Yogyakarta.…”
Section: Resultsmentioning
confidence: 99%